The Landscapes Drawn During the Expeditions of Ivan Honchar: Chernihiv and Chernihiv region (1957–1959) - Дубиківська-Кальненко, Лідія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The article analyzes for the first time the paintings of Ivan Honchar (1911-1993), People’s Artist of Ukraine, created during the planned expedition to Chernihiv (1957) and subsequent trips to Chernihiv region in 1957-1959. The artist’s manner is determined as realistic-impressionistic. It was established that the works of this cycle are united by the theme "historical landscape" and are the integral part of Ivan Honchar’s "Picturesque Ukraine". Actually, the landscapes of Chernihiv region gave start to the cycle of "Picturesque Ukraine", written on travels by Ukraine. The works are drawn the principle of ethnographic and administrative division. The study of Ivan Honchar’s daily records demonstrates that the creation of the artistic image of Chernihiv and Chernigiv region, together with artifacts of folk art of the region, marked the beginning of the collection which later became the base of Ivan Honcharas’ home museum in 1959.